Paclitaxel-incorporated nanoparticles improve functional recovery after spinal cord injury - Zhang, Xinzhu; Xiong, Wu; Kong, Guang; Zhen, Yushan; Zeng, Qiang; Wang, Siming; Chen, Sheng; Gu, Jun; Li, Cong; Guo, Kaijin (Frontiers in Pharmacology, 2022)
As a worldwide medical problem, spinal cord injury has no clear and effective treatment to improve its prognosis. Hence, new treatment strategies for spinal cord injury with good therapeutic efficacy have been actively pursued. As a new drug loading system, acetal dextran nanoparticles (SAD) have good biocompatibility and biodegradability. Therefore, we designed spermine-functionalized acetal-dextran (SAD) nanoparticles and encapsulated paclitaxel (PCL) into them. This design can ensure the sustained release of paclitaxel in the injured area for 4 days and promote the extension of nerve processes in vitro. In our experiment, we found that paclitaxel-loaded SAD nanoparticles (PCL@SAD) decreased the level of chondroitin sulfate proteoglycan in the rat spinal cord injury model, which reduced the scar repair of the injured site and changed the inhibitory environment after spinal cord injury. This reveals that PCL@SAD can effectively protect the injured spinal cord and ultimately improve the functional recovery of the injured spinal cord. One single injection of PCL@SAD shows better therapeutic effect than that of PCL. This study opens an exciting perspective toward the application of neuroprotective PCL@SAD for the treatment of severe neurological diseases.